Bohaterki słowiańskiej historii. Królowe, kapłanki i ofiarnice w utworach Juliusza Słowackiego (na wybranych przykładach) = The heroine of the Slavic history. Queens, priestesses and sacrifices in Juliusz Słowacki`s works (based on chosen examples) - Ruszczyńska, Marta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article is an attempt to show feminine figures in the context of the Slavic history. Chosen examples were selected mainly from the Słowacki`s dramas. They are placing themselves around the Slavic myth of the beginning. The priestess and sacrifice from the drama "Lilla Weneda" are two the most complementary representatives of Sisters figures next to the figure of legendary Wanda.
Keywords: Slav history; myth; sacrifice; słowiańszczyzna; mit; ofiara